Measurement of the bulk radioactive contamination of detector-grade silicon with DAMIC at SNOLAB. (21st June 2021) - Aguilar-Arevalo, A.; Amidei, D.; Baxter, D.; Cancelo, G.; Cervantes Vergara, B.A.; Chavarria, A.E.; Darragh-Ford, E.; D'Olivo, J.C.; Estrada, J.; Favela-Perez, F.; Gaïor, R.; Guardincerri, Y.; et al.
Abstract: We present measurements of bulk radiocontaminants in the high-resistivity silicon CCDs from the DAMIC experiment at SNOLAB. We utilize the exquisite spatial resolution of CCDs to discriminate between α and β decays, and to search with high efficiency for the spatially-correlated decays of various radioisotope sequences. Using spatially-correlated β decays, we measure a bulk radioactive contamination of 32 Si in the CCDs of 140 ± 30 μBq/kg, and place an upper limit on bulk 210 Pb of < 160 μBq/kg. Using similar analyses of spatially-correlated α and β decays, we set upper limits of < 11 μBq/kg (0.9 ppt) on 238 U and < 7.3 μBq/kg (1.8 ppt) on 232 Th in the bulk silicon. The ability of DAMIC CCDs to identify and reject spatially-coincident backgrounds, particularly from 32 Si, has significant implications for the next generation of silicon-based dark matter experiments, where β's from 32 Si decay will likely be a dominant background.